2020
DOI: 10.1109/access.2020.3024942
|View full text |Cite
|
Sign up to set email alerts
|

Robustness of Complex Networks Considering Attack Cost

Abstract: Robustness of complex networks has attracted much attention in diverse disciplines. Most of previous studies did not consider the attack cost. In this paper, the network robustness is studied with the consideration of attack cost, with different complex network models and different robustness indices. It is found that with different cost function and attack budget, the best attack strategy changes. When the budget is low and attacking hubs costs much more than attacking an unimportant node, then the high-degre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…It is also of interest when practical limitations such as cost is taken into consideration as the attack cost has often found to be positively correlated to the node degree [26]. Practical network dismantling strategies minimizing attack cost have attracted considerable research attention recently [27,28,29,30].…”
Section: Network Under Attack With Limited Knowledgementioning
confidence: 99%
“…It is also of interest when practical limitations such as cost is taken into consideration as the attack cost has often found to be positively correlated to the node degree [26]. Practical network dismantling strategies minimizing attack cost have attracted considerable research attention recently [27,28,29,30].…”
Section: Network Under Attack With Limited Knowledgementioning
confidence: 99%
“…In the case of studying complex networks that reflect real objects, the need arises for a quantitative assessment of the damage resulting from the realization of an adverse event of uncertainty. When considering a network in statics, these include vulnerability and reliability [21][22][23]. Reliability measures the extent to which a network is able to withstand such an event without degrading its performance.…”
Section: Introductionmentioning
confidence: 99%
“…Typically, methods to assess the robustness of complex networks mainly consider random or deliberate attacks on the network structure and complex networks with cascading failures. In analyzing the robustness of complex networks, scholars have come up with rich results: Wang et al [15] found that the optimal attack strategy changes with different cost functions and attack methods considering the cost of the attack.Ratnayake, P et al [16] proposed to evaluate the robustness of complex networks considering not only the topology but also the fitness function and fitness distribution among nodes. Many scholars have proposed some robustness metrics for specific systems.…”
Section: Introductionmentioning
confidence: 99%